Effectual Truth and the Machiavellian Enterprise - Dustin Gish (Literature)
The political philosophy of Niccolò Machiavelli has often been reduced to the statement that ‘the end justifies the means’ and understood as an expression of realpolitik as a result of his pragmatic, even ruthless, counsel to would-be princes, or political leaders. However, a more nuanced understanding of Machiavelli’s reflections on human nature in his writings, especially The Prince, reveals that there is a philosophic core within his approach to political success, the acquisition and maintenance of state. But while there is no doubt that Machiavelli openly rejected the idealism of certain ancient and medieval thinkers, whose imagined republics only ever existed in theory, and instead candidly advised princes to seek and wield power, his work reflects not only a profound engagement with the harsh realities of a political landscape dominated by practical necessity but also a project of far-reaching scope. With the concept of “effectual truth” as his guide, Machiavelli proposes radical means to overcome fortuna with virtù and establish the foundations of power in order to bring about that conquest. The fulfillment of his mission and mandate to those who follow his lead represents the Machiavellian enterprise.